Plantar Fasciitis: Clinical Aspects - Andreas Stevan (PT Kalbe Farma Tbk., 2020)
Plantar fasciitis is a common degenerative disease involving connective tissue in heel pad area, indicated with exquisite pain and tenderness over the plantar medial tuberosity of the calcaneus at the proximal insertion of the plantar fascia. The pain often worse in the morning and gradually decreases during the day. The incidence is highest among active adults. A common misconception is that pain is caused by the bone spurs bulging from the heel and “digging” into the surrounding tissue; the pain is actually caused by the micro tears and inflammation due to stiffness. Most cases resolve regardless of therapies given. Nonsurgical and surgical treatments are available as indicated. Plantar fasciitis merupakan penyakit degeneratif umum melibatkan jaringan ikat daerah tumit kaki yang ditandai nyeri khas di daerah tuberositas plantar medial kalkaneus pada insersi proksimal plantar fascia. Nyeri umumnya dirasakan pada pagi hari saat bangun tidur dan berkurang setelah beraktivitas. Kondisi ini sering terjadi pada orang dewasa aktif. Miskonsepsi yang sering dikaitkan dengan tulang tumbuh yang “menusuk” jaringan lunak di sekitar insersi fascia, padahal lebih dikaitkan dengan sobekan mikroskopis dan inflamasi karena kekakuan jaringan ikat. Kebanyakan kasus sembuh sendiri tanpa pengobatan. Terapi non-bedah atau bedah sesuai penyebab dan indikasi.